A Z-Source Network Integrated Buck-Boost PFC Rectifier - Mohammad Monfard (International Journal of Industrial Electronics, Control and Optimization, 2019)
This paper presents a wide range gain buck-boost type PFC rectifier based on the conventional buck-boost DC-DC converter. This novel rectifier is fed by a buck-type Z-source network at the DC side with the help of an inductor smoothing the AC side input current. The proposed PFC rectifier offers better input and output waveform qualities compared to the conventional buck-boost PFC rectifier. Maintaining near to unity power factor (PF) and low total harmonic distortion (THD) in a wide range of load variations and also the simple single-loop control are the main features of the proposed PFC rectifier. Furthermore, the switching frequency of the proposed rectifier can be chosen very higher than the competitors, since it successfully lets incredibly increase the duty cycle for a same voltage gain compared to the traditional solutions. This leads to reduced size of passive components and volume of the rectifier. A 250 W prototype circuit is designed and simulated considering most practical issues to evaluate the performance of the proposed PFC in both buck and boost modes. The results are compared with some of the well-known conventional PFC rectifiers that confirm the superior performance of the proposed topology.